How to Cope With Post-Game Depression - Schriefer, Natalie (Wired, 2022)
Congratulations, you beat your favorite video game. Now it’s time to beat the feelings of emptiness.
Section: tags
Keywords: dept.hhs; gaming culture; mental health; psychology; video games